Tradisi Sinoman Masyarakat Desa Ngampel Dalam Perspektif Tindakan Sosial Max Weber - Nur Aswin, Risma; Dwi Astutik; Yosafat Hermawan Trinugraha (Jurnal Niara, 2024)
Traditions that exist in society are one of the things that will continue to exist, so their existence must be preserved by community members. One of the typical traditions possessed by Indonesian citizens is the tradition of mutual cooperation. One of the traditions of mutual cooperation in rural communities that still exists today is the sinoman tradition. The sinoman tradition in Ngampel Village has experienced a decline in participation from the village's youth. The decline in participation was due to the many services offered to help during the celebration process. This research uses a qualitative research method with a case study approach. Research data was obtained from primary data originating from observations and interviews. Meanwhile, secondary data was obtained from literature study. The results of the research show that people's lives are starting to change, making people have a choice in participating in activities at weddings. Changes in roles in youth participation in the Sinoman tradition are caused by the burdens and responsibilities that these youth have. Apart from that, it is also caused by changes in thinking patterns and technological advances which make many things more practical and efficient.